Therapeutic analysis of cannabidiol for Alzheimer treatment - Magalhães, Maria Vitória Frota (2024)
Objective: To analyze therapeutic evidence regarding the potential antioxidant, anti-inflammatory and neuroprotective effects of cannabidiol (CBD) and its effectiveness for the treatment of Alzheimer's Disease (AD). Methodology: Data collection, in the Virtual Health Library, targeting the primary databases Medical Literature Analysis and Retrieval System Online (Medline) and Latin American and Caribbean Literature in Health Sciences (Lilacs) to answer the research question: is the therapeutic use of cannabidiol effective in improving the treatment of patients with Alzheimer's Disease? Results: 14 articles were selected, after analyzing the inclusion and exclusion criteria, all after 2017, with the largest number concentrating on systematic literature review or meta-analysis. Conclusion: Cannabidiol has clear potential to reduce the symptoms of AD given its action on the Central Nervous System. Therefore, its therapeutic use in the treatment of AD emerges as a promising field of investigation, highlighting its relevance as a safe and effective treatment option. Therefore, an in-depth understanding of the antioxidant, anti-inflammatory and neuroprotective properties of CBD is necessary, not only for a better clinical definition of AD, but also for a series of neurological diseases that still have undefined treatments. The potential of CBD, therefore, represents a valuable alternative in the context of neurology, offering significant perspectives for the treatment of neurodegenerative conditions.